Evaluation of the protective capacity of new mild Citrus tristeza virus (CTV) isolates selected for a preimmunization program (Scientia Agricola, 2013)
The use of tolerant rootstocks and preimmunization has satisfactorily controlled losses associated with the Citrus tristeza virus (CTV). Several researchers have shown that CTV mild isolates that are selected in the same region where they are used are superior to isolates obtained from other areas. Thus, budwoods of 20 outstanding citrus trees were collected in north and northwestern Paraná state (Brazil) citrus-producing areas and established to be used in a preimmunization program. These budwoods were tested to evaluate the potential protection of the inherently present viral complex. Based on biological indexing and molecular characterization of the capsid protein gene by RFLP (restriction fragment length polymorphism, which indicated that the plants were infected with mild isolates of CTV), some of the selected plants could be used in a preimmunization program. These potentially mild and protective isolates were challenged with severe 'Rolândia' isolate inoculations by grafting and by the brown citrus aphid (Toxoptera citricida Kirkaldy) vector, which was faster in transmitting the virus. Some isolates had a better protective value than others, particularly when challenged with the severe CTV isolate. The SSCP (single strand conformational polymorphism) molecular analysis was an excellent complementary tool for monitoring the performance of the experiments and the stability of the viral complex present in the plants. Isolate number 1, collected in the municipality of Cruzeiro do Sul (CS-1), was the most promising for protecting commercial Pêra sweet orange (C. sinensis L.) orchards in northern and northwestern Paraná. The Rolândia severe CTV isolate was stable and had a high genetic divergence among the severe isolates used as a control (Capão Bonito and Barão B) and all of the isolates tested.